(untitled) (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2024)
Background: Several studies have confirmed the importance of using the body condition assessment process in dairy cow breeding stations, as it is one of the means that helps in the success and efficiency of the management used, improving feeding programs and monitoring the health status of the cows, thus increasing pregnancy and production rates in the herd. Materials and Methods: The study conducted at the Diwaniyah cows station included Holstein cows in parity 2, were classified according to body condition at calving into a 2.5–3 point (BCS1) Included 17 cows, a 3-4 point (BCS2) Included 20 cows, and a 4-5 point (BCS3) Included 13 cows Depending on the 1-5 grade scale for dairy cows. Production was recorded weekly during the study, The percentages of its components were determined at peak production and three months after calving. Results: BCS2 group was significantly superior (P≤0.01) in average daily and total production compared to the other groups. BCS2 and BCS3 groups were significantly superior (P≤0.01) in the average daily production at the peak compared to BCS1 group. BCS3 group was significantly superior (P≤0.05) in lactose concentration at peak production, and in the concentration of lactose and protein after three months of production compared to BCS1 group. Conclusions: Body condition at calving affects the productive performance of cow. Body condition assessment determines the energy reserve in the body during the production cycle to prepare the appropriate nutritional program, meet production requirements, maintain the health of cows, and protect them from metabolic diseases.